Knowledge, attitudes, and practices of community pharmacists toward the management of acne vulgaris in Saudi Arabia - Alrabiah, Ziyadh; Wajid, Syed; Babelghaith, Salmeen D.; Al Arifi, Mohamed N. (Frontiers in Medicine, 2023)
Background and objectives In Saudi Arabia, Acne vulgaris is a very predominant ailment and Pharmacists currently have standardized protocols at their disposal for the treatment of acne. Pharmacists often prescribe medications for minor cases of acne. Therefore, this study aimed to explore community pharmacists (CPs)’ knowledge, attitudes, and practice toward acne management in Riyadh, Saudi Arabia. Methods An online cross-sectional study was conducted among CPs working in Riyadh, Saudi Arabia from January and April 2021, using a self-administered, questionnaire, was divided into four sections that collected information from the CP’s Knowledge, attitudes, and practices and the management of acne vulgaris. The data were analyzed using the Statistical Package for the Social Sciences version 26 (SPSS). Result A total of 313 CPs were enrolled in the study who successfully returned the questionnaire. The mean score of knowledge on etiology, pathophysiology, and therapy for AV was 5.3 ± (SD = 1.5). However, the majority of CPs had a moderate level of knowledge (80.8%), followed by mild to moderate (12.8%). This study showed that CPs had an insufficient level of knowledge about ace management, about 6% of CPs have a high level of knowledge. Inadequate knowledge was revealed in their management practice, only 0.3% of CPs treated patients with acne on their own without a referral. In addition, CPs showed a positive attitude toward acne management. Conclusion There is a need to improve CPs’ understanding of acne care and to contribute to participating in organized training sessions on the management of AV.